(untitled) (NTU Journal of Agriculture and Veterinary Science, 2024)
Root rot and seedlings damping-off disease caused by Rhizoctonia solani is the most damaging disease of cucumber. This disease causes reducing yield in cucumber. This study conducted laboratory and greenhouse conditions to find out the efficacy of biological control agents, Trichoderma harzianum, Bacillus subtilis, the chemical compound Bion, and fungicide revanol. The results of pathogenicity test of R. solani on cucumber seeds showed that R. solanihas led to a significant reduction in the percentage of germination and seed rot compared to the control treatment, which amounted to 100%. The results showed the ability of all control agents used in this study to reduce the incidence of the disease. The Bion (benzothiadiazole) treatment showed significant effect and outperformed the other treatments in increasing the activity of the peroxidase enzyme, which was recorded at 14,440 (unit. minute-1.g wet weight-1). It also achieved the highest significant increase in total phenolics 1.52 (mg -1 . gram wet weight -1). Biological control agent T. harzianum has outperformed on other treatments in causing an increase in the activity of the polyphenol oxidase enzyme, it has recorded 1811.7 (unit. minute - 1 .gram of wet weight - 1 leaf).